2015
DOI: 10.1155/2015/916385
|View full text |Cite
|
Sign up to set email alerts
|

Intrastromal Corneal Ring Segment Implantation (Keraring 355°) in Patients with Central Keratoconus: 6-Month Follow-Up

Abstract: We evaluate the efficacy and safety of Keraring 355° intrastromal corneal ring segment (ICRS) implantation aided by PocketMaker microkeratome for the correction of keratoconus. Patients underwent ICRS insertion using mechanical dissection with PocketMaker microkeratome and completed 6 months of follow-up. Uncorrected visual acuity (UCVA), best spectacle-corrected visual acuity (BSCVA), refraction, topographic findings, safety, efficacy index, and adverse events were reported for six months postoperatively. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
51
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 44 publications
13
51
1
Order By: Relevance
“…Considering primary spherical error, As Pinero et al [19] mentioned, mechanical method to implant intrastromal segment can result in negative increase in spherical error, our study shows increase in a negative direction which accords with previous studies [25][26][27][28]. Secondary spherical error and quadrafoil also showed significant increase despite secondary astigmatism error which remained the same.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Considering primary spherical error, As Pinero et al [19] mentioned, mechanical method to implant intrastromal segment can result in negative increase in spherical error, our study shows increase in a negative direction which accords with previous studies [25][26][27][28]. Secondary spherical error and quadrafoil also showed significant increase despite secondary astigmatism error which remained the same.…”
Section: Discussionsupporting
confidence: 89%
“…At the next step, suction ring was removed and Keraring 355 was implanted in the pocket. The surgeon chose the suitable thickness for Keraring 355 based on a pre-designed nomogram; a custom-surgeon nomogram [26]. The cornea was covered by a silicone-hydrogel bandage contact lens (Bausch & Lomb).…”
Section: Surgical Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…This finding is much better than that reported for keratoconic eyes treated with photorefractive keratectomy (PRK) 13 in which the authors found that the refractive readings obtained with two automated devices varied more from subjective refraction after treatment with PRK. This could be due to the fact that compared with PRK, keraring insertion technique is minimally invasive and the technique was designed to regularize the corneal surface, improve visual acuity, and reduce refractive errors 38,39 or it may be due to the different pupil analysis diameters used by the autorefractors which were suggested to influence the agreement between refractive techniques. 40 The visual acuity measured with subjective refraction increased from 0.1860.14 logMAR preoperatively to 0.1060.10 logMAR postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Keratoconus incidence is 1 of 2000 persons. Keratoconus is a multifactorial disease of unknown etiology, which impairs visual quality of the cornea because of thinning and protrusion, resulting in an irregular astigmatism with or without myopia (Jadidi et al, 2015). Change of corneal shape for keratoconus patients can change the optical quality of the eye and retinal image quality.…”
Section: Introductionmentioning
confidence: 99%